Mitigation of acetaminophen-induced liver toxicity by the novel phosphatidylinositol 3-kinase inhibitor alpelisib - Shaker, Mohamed E.; Gomaa, Hesham A. M.; Hazem, Sara H.; Abdelgawad, Mohamed A.; El-Mesery, Mohamed; Shaaban, Ahmed A. (Frontiers in Pharmacology, 2023)
The sterile inflammatory response mediated by Toll-like receptors (TLRs) 4 and 9 is implicated in the massive hepatic damage caused by acetaminophen (APAP)-overdose. There is a crosstalk between TLR-dependent signaling with other intracellular kinases like phosphatidylinositol 3-kinases (PI3Ks). Nevertheless, the detailed role of PI3Kα is still unknown in hepatic sterile inflammation. Accordingly, the effect of the novel PI3Kα inhibitor alpelisib was investigated in the setting of APAP-driven sterile inflammation in the liver. This was examined by pretreating mice with alpelisib (5 and 10 mg/kg, oral) 2h before APAP (500 mg/kg, i.p.)intoxication. The results indicated that alpelisib dose-dependently lowered APAP-induced escalation in serum liver function biomarkers and hepatic necroinflammation score. Alpelisib also attenuated APAP-induced rise in cleaved caspase 3 and proliferating cell nuclear antigen (PCNA) in the liver hepatocytes, as indices for apoptosis and proliferation. Mechanistically, inhibition of PI3Kα by alpelisib limited APAP-induced overproduction of the pro-inflammatory tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6 in the blood circulation via switching off the activation of several signal transduction proteins, including extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), signal transducer and activator of transcription-3 (Stat-3), glycogen Synthase Kinase (GSK)-3β and nuclear factor (NF)-κB. Alpelisib also impaired APAPinstigated immune cell infiltration in the liver via reducing systemic granulocyte/macrophagecolony stimulating factor (GM-CSF) release and reversed APAP-induced abnormalities in the systemic and hepatic levels of the anti-inflammatory IL-10 and IL-22. In conclusion, selective modulation of the PI3Kα activity by alpelisib can hinder the inflammatory response and infiltration of immune cells occurring by APAP-hepatotoxicity.